Clinical pharmacokinetics of kavalactones after oral dosing of standardized kava extract in healthy volunteers. (28th October 2022) - Kanumuri, Siva Rama Raju; Mamallapalli, Jessica; Nelson, Robyn; McCurdy, Christopher R.; Mathews, Carol A.; Xing, Chengguo; Sharma, Abhisheak
Abstract: Ethnopharmacological relevance: Piper methysticum G. Forst. (Piperaceae), commonly known as kava, has been used as a traditional beverage for centuries for its relaxing properties. Kavalactones are considered to be the major constituents responsible for kava's beneficial effects. Despite the extensive use of kava, clinical pharmacokinetic data is not available in the literature; therefore, the findings of this study will be critical for the dosage calculations for future clinical evaluation of kava. Aim of the study: The aim of the current study is to examine the clinical pharmacokinetics of six major kavalactones following oral dosing of flavokavain A/B-free standardized kava extract capsules in healthy volunteers using two dosage regimens. Materials and methods: A sensitive, reliable, and specific ultra-high pressure liquid chromatography-mass spectrometry (UPLC-MS/MS) method was developed and validated for the simultaneous quantification of six major kavalactones (kavain, dihydrokavain, methysticin, dihydromethysticin, yangonin, and desmethoxyyangonin) and two flavokavains (A and B) in human plasma. Pharmacokinetic profiles were assessed in ten healthy volunteers after oral doses of standardized kava product, and plasma samples were analyzed for six kavalactones and two flavokavains using the validated UPLC-MS/MS method. Concentration-time data was subjected to pharmacokinetic analysis. Results: The systemic exposure of the kavalactones was found to be in the following order: dihydrokavain > dihydromethysticin > kavain > methysticin > yangonin. Desmethoxyyangonin was quantifiable only at a couple of time points, while flavokavain A and flavokavain B were not present in any of the plasma samples. Fast absorption of five kavalactones was observed with time to reach the maximum plasma concentration of 1–3 h. A dose proportionality in pharmacokinetics was established from 75 to 225 mg of kavalactone doses. In the multiple-dose study, a significant reduction in the extent of absorption of kavalactones with food was observed. Conclusion: Single and multiple-dose clinical pharmacokinetic studies for kava were performed in healthy volunteers, and higher exposure to the kavalactones was observed after single-dosing (225 mg), while a longer duration of exposure was observed after three times a day (3 x 75 mg) dosing. Graphical abstract: Image 1 Highlights: A bioanalytical method has been developed for the simultaneous analysis of six major kavalactones and two flavokavains. A clinical pharmacokinetic study of kavalactones was performed in healthy volunteers for the first time. Food intake altered the absorption of kavalactones and lowered their systemic exposure.